2009
DOI: 10.1017/s002211200900682x
|View full text |Cite
|
Sign up to set email alerts
|

Lagrangian drift near a wavy boundary in a viscous oscillating flow

Abstract: The formation of sand ripples in oscillating flows is thought to be due to a steady streaming current which near the bottom is towards the crests. We present quantitative observations of this mean flow over self-formed and artificial ripples, by observing the displacement of a coloured filament after a number of oscillations in the simple situation of viscous Couette flow. Confusingly, the filament moves in the ‘wrong’ direction, because it follows the Lagrangian mean flow. We calculate the Lagrangian mean flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…36 More recently, Larrieu et al observed Lagrangian drift for oscillatory flow over a wavy wall due to streaming. 34 Wang and Ottino observed that increasing K C increases disorder in tracer motion in a lid-driven cavity flow. 43 The present finding is unique to low-Re open cavity flows directly applicable to dispersion in acinar airways with a large displacement parameter, K C .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…36 More recently, Larrieu et al observed Lagrangian drift for oscillatory flow over a wavy wall due to streaming. 34 Wang and Ottino observed that increasing K C increases disorder in tracer motion in a lid-driven cavity flow. 43 The present finding is unique to low-Re open cavity flows directly applicable to dispersion in acinar airways with a large displacement parameter, K C .…”
Section: Discussionmentioning
confidence: 99%
“…27,[31][32][33][34][35][36][37] In an oscillatory flow setting, a nonzero mean flow averaged over one time period may be observed. This nonzero mean flow can result in significant drift of particles at end cycle called steady streaming.…”
Section: B Eulerian Streaming Stokes Drift and Lagrangian Drift Vementioning
confidence: 99%
See 2 more Smart Citations
“…Because of the identical scaling of the two contributions u str and u Sto , it is difficult in general to anticipate which of streaming or Strokes drift contribute more to this Lagrangian mean flow [22]. Predicting the structure of the Lagrangian mean flow in the orbital sloshing configuration is a difficult task, not only because of the non-trivial viscous boundary layers that generate the streaming, but also because of the complex dynamics near the contact line.…”
mentioning
confidence: 99%